Whipple's disease: A case report - Popović Dušan Đ.; Špuran Milan; Jovanović Ivan; Alempijević Tamara; Đuranović Srđan; Kovačević Nada; Micev Marjan; Krstić Miodrag (Vojnosanitetski Pregled)
Introduction. Whipple's disease is a chronic, multisystem, infectious disease caused by Tropheryma whipplei. It most commonly affects Caucasian males, middle-aged. Morbus Whipple is primarily gastrointestinal disease, manifested as malabsorption syndrome, and diagnosed by endoscopy and intestinal biopsy. Extraintestinal manifestations are not rare. Case report. A 48-year-old male was admitted due to diarrhea, weight loss and weakness in the extremities. Physical examination findings pointed out diffuse hyperpigmentation, pleural effusion and leg edema. Anemia, inflammatory syndrome and malabsorption signs were discovered through laboratory tests. The diagnosis was confirmed by intestinal biopsy. The patient was treated with antibiotic and symptomatic therapy. After 9 months, the patient had no symptoms, and clinical and laboratory findings were regular. Conclusion. Whipple's disease is a rare disease. A high degree of clinical suspicion for the disease (malabsorption, arthritis, fever, neurological symptoms) is the most important for diagnosis. Timely diagnosis and appropriate therapy prevent the disease progression and fatal outcome.